Women's health, public policy, and community action - Mukhopadhyay, Swapna (Manohar Publishers & Distributors, 1998)
Contributed articles presented at the National Seminar on Women's Health and Reproduction held at India International Centre, New Delhi in Nov. 1995; with special reference to Indian women.